Use of herbal to reduce nausea and vomiting in pregnancy: a systematic review - Mutiara Solechah; Nita Adhani Pasundani; Dewi Nurdianti (Sean Institute, 2024)
Nausea and vomiting in pregnancy are discomforts that are estimated to occur in 70-80% of pregnant women. Some pregnant women usually avoid chemical or conventional drugs as far as possible due to concerns about potential teratogenic effects, so there is an increasing trend towards alternative treatments. The use of herbal medicines is often not reported to health professionals and health professionals rarely question the use of herbal medicines. Lack of knowledge about potential toxicities and ability to interact with conventional treatments may impact the mother and fetus . This article discusses herbs that have the potential to relieve symptoms of nausea and vomiting using a systematic review method by searching, collecting, filtering and reviewing related articles that meet the inclusion and exclusion criteria. This article uses two databases, namely Pubmed and Sciencedirect. It can be concluded that ginger, peppermint, lemon, quince, pomegranate, chamomile and cardamom can be used as alternative herbal choices to reduce nausea and vomiting and are safe for consumption by pregnant women at the appropriate dose.